Public participation in lower and higher socio-economic areas in South Africa - Lindeque, A. S.; Cloete, C. E. (University of the Free State, 2005)
A prominent feature of public life in South Africa the last decade has been an increasing demand for more participation in the formulation and making of decisions affecting the public’s quality of life. This demand has also become a focus of political activism. Public participation in plan formulation and in decision making has to be seen as a reality, and not as an optional extra. It can be argued that unless plan formulation and decision making take cogni sance of different political traditions and cultures and are inclusive and parti cipatory it has little chance of producing long lasting solutions. The aim of this research is to compare the public participation process in a lower socio economic area with that in a higher socio economic area to de termine if the process and focus of the public participation process differ in accordance with the socio economic status of an area. The study compares the public participation process in two case studies: the Mabopane and Muckleneuk areas in Pretoria, with specific reference to the Mabopane Inter modal Facility Redevelopment Project and the Gautrain Rapid Rail Project going through the Muckleneuk neighbourhood, respectively. Findings indicate that the driving force for participation in the higher socio economic areas is based on the effect that the proposed development plan ning would have on the area as a whole, whereas the focus of public partici pation process in the area with a lower socio economic status tends to be on the influence on job creation and the impact it has on the affected individual.

’n Uitstaande kenmerk van openbare lewe in Suid Afrika gedurende die af gelope dekade was ’n toenemende aandrang vir groter deelname aan die formulering en neem van besluite wat die lewenskwaliteit van die publiek raak. Hierdie aandrang het ook ’n fokuspunt van politieke aktivisme geword. Open bare deelname in planformulering en besluitneming moet as ’n realiteit gesien word en nie as ’n opsionele ekstra nie. Daar kan geredeneer word dat indien planformulering en besluitneming nie kennis neem van die onderskeie politieke tradisies en kulture en ook inklusief en deelnemend is nie, dit weinig kans sal hê om blywende oplossings te skep. Die doel van hierdie navorsing is om die openbare deelnemingsproses in ’n laer sosio ekonomiese gebied te vergelyk met diè in ’n hoër sosio ekono miese gebied, om te bepaal of die proses en die fokus van die publieke deelnemingsproses verskil volgens die sosio ekonomiese status van ’n gebied. Die studie vergelyk die openbare deelnemingsproses in twee gevallestudies: die Mabopanegebied en Muckleneukgebied in Pretoria, met spesifieke ver wysing na die Mabopane Inter modale Fasiliteitsherontwikkelingprojek en die Gautrain Sneltreinprojek wat deur die Muckleneuk woonbuurt gaan, onder skeidelik. Bevindings toon aan dat die dryfveer vir deelname in die hoër sosio ekonomiese gebied gebaseer is op die effek wat die voorgestelde ontwik kelingsbeplanning sal hê op die gebied as ’n geheel. Openbare deelname in die gebied met ’n laer sosio ekonomiese status, daarteenoor, is gefokus op die effek op werkskepping asook die impak wat dit op ’n indiwidu het.
Keywords: Planning; Public participation process; Socio economic areas; Stakeholders